Xenophon’s political philosophy: a project for the whole of Greece - Jaskelevičius, Alius (Literatūra, 2018)
[full article, abstract in English; abstract in Lithuanian]This paper discusses Xenophon’s political philosophy and its Greek context. One of the major themes running through Xenophon’s works is leadership, which he tackles implicitly or explicitly in virtually all of his writings (be it his philosophical, historical or literary writings). For Xenophon, the leader was important not only as an individual leading the armed forces, but as a leader of a city or a community as well. Bearing in mind the importance of leadership and the role of leaders for Xenophon, the author of this paper tries to show that Xenophon’s political philosophy can be seen as part of his Panhellenic program. The aim of this program is to politically unite the Greeks by making them enter into an alliance in the name of a common Panhellenic crusade against Persia.
Keywords: Xenophon; Panhellenism; leadership; Cyrus the Younger; Anabasis; Hellenika